The Elasticity of Poverty to the Growth and Inequality Before and During the Covid-19 Pandemic - Ahmadi Murjani (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
This study aims to measure the elasticity of poverty to income growth and inequality and to assess the pro-poorness of the growth near and during the Covid-19 pandemic by taking the South Kalimantan province of Indonesia as a focused study. The lack of poverty elasticity and decomposition study during the Covid-19 pandemic has motivated this study to be done. By using the poverty decomposition method applied to South Kalimantan data, this study achieved some conclusions. First, all the poverty measurements (FGT indexes) have the absolute value of elasticities by more than one, indicating that poverty is highly sensitive to the change of income growth and inequality. Second, when inequality is constant, an increasing growth rate of income will benefit the poor more than the less poor, and selecting the poverty measurement to observe is critical. Third, the trade-off between growth and inequality represented by MPRS is positive and more than one in all years of examination. There should be more growth rate needed to respond to an increasing inequality to maintain the poverty rate stable. Forth, the targeted policies to the poor in the period from 2020 to 2021 are proven to help the poor shown by the Poverty Growth Curve.